2012
DOI: 10.1590/s0037-86822012000500007
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance genes, including blaKPC and blaCTX-M-2, among Klebsiella pneumoniae isolated in Recife, Brazil

Abstract: Introduction:The prevalence of cephalosporins and carbapenem-resistant Klebsiella pneumoniae strains is rising in Brazil, with potential serious consequences in terms of patients' outcomes and general care. Methods: This study characterized 24 clinical isolates of K. pneumoniae from two hospitals in Recife, Brazil, through the antimicrobial susceptibility profile, analyses of β-lactamase genes (bla TEM, bla SHV, bla CTX-M , bla KPC , bla VIM , bla IMP, and bla SPM ), plasmidial profile and ERIC-PCR (Enterobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 30 publications
8
29
0
1
Order By: Relevance
“…We also observed that the frequency and diversity of class 1 integrons in the K. pneumoniae clinical isolates in Recife increased between 1998 and 1999 and between 2007 and 2008. This result is consistent with the observed rapid dissemination of beta-lactamase genes along with resistance to extended-spectrum cephalosporins and carbapenems among K. pneumoniae clinical isolates in Recife in recent years 35 . In this study, the diversity of class 1 integrons in K. pneumoniae isolates from Recife, Brazil favors the dissemination of resistance among K. pneumoniae and other species in the hospital environment.…”
Section: Antimicrobial Resistancesupporting
confidence: 89%
“…We also observed that the frequency and diversity of class 1 integrons in the K. pneumoniae clinical isolates in Recife increased between 1998 and 1999 and between 2007 and 2008. This result is consistent with the observed rapid dissemination of beta-lactamase genes along with resistance to extended-spectrum cephalosporins and carbapenems among K. pneumoniae clinical isolates in Recife in recent years 35 . In this study, the diversity of class 1 integrons in K. pneumoniae isolates from Recife, Brazil favors the dissemination of resistance among K. pneumoniae and other species in the hospital environment.…”
Section: Antimicrobial Resistancesupporting
confidence: 89%
“…Until 2005, the geographical distribution of these enzymes in members of the family Enterobacteriaceae -K. pneumoniae, in particular -was limited to the eastern part of the United States. In Brazil, KPC has been described since 2006, and it was fi rst reported in K. pneumoniae isolates from Recife (2) , followed by reports (3) in other species from the Enterobacteriaceae and non-fermenting bacilli (4) (5) (6) . Carbapenem resistance in Proteus mirabilis caused by KPC-2 was also fi rst reported in the United States (7) in 2008, and currently, there are a few reports of P. mirabilis KPC producers worldwide (8) (9) .…”
mentioning
confidence: 99%
“…Plasmid DNA was extracted by the UltraClean Endotoxin-Free Mini Plasmid Prep Kit (Mo Bio Lab, Carlsbad, CA, USA) and was visualized and analyzed by electrophoresis on a 0.7% agarose gel. The molecular weight of each plasmid was determined by comparison with plasmids of known molecular weight, e.g., with that of K. pneumoniae K16-P strain (3) . Five plasmids with estimated molecular sizes of >150kb, 150kb, 120kb, 90kb, and 70kb were identifi ed in the isolate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such an understanding of these relationships may also further our understanding of the behavior of endemic pathogens (e.g., A. baumannii) when challenged with the introduction of emerging agents (e.g., carbapenem-resistant enterobacteria) 25,26 . Our study found a negative association between the incidence of A. baumannii and the incidences of both S. aureus and Enterobacter spp.…”
Section: Ethical Considerationsmentioning
confidence: 99%